2020
DOI: 10.1101/2020.07.23.218024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Competitive Microtubule Binding of PEX14 Coordinates Peroxisomal Protein Import and Motility

Abstract: PEX14 functions as peroxisomal docking protein for the import receptor PEX5. For docking, the conserved N-terminal domain of PEX14 (PEX14-NTD) binds amphipathic alpha-helical ligands, typically comprising one or two aromatic residues, of which human PEX5 possesses eight. Here, we show that the PEX14-NTD also binds to microtubular filaments in vitro with a dissociation constant in nanomolar range. PEX14 interacts with two motifs in the C-terminal region of human ß-tubulin. At least one of the binding motifs is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…In 2019, Barros-Barbosa et al showed that rat PEX14 is an intrinsic membrane protein with an N-in C-out topology (Barros-Barbosa et al, 2019; Reuter et al, 2021). Myc-tagged N-and C-terminal truncations of Pex14 were tested for localization to LDs or peroxisomes in +Oleate cells (Figure 4G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Barros-Barbosa et al showed that rat PEX14 is an intrinsic membrane protein with an N-in C-out topology (Barros-Barbosa et al, 2019; Reuter et al, 2021). Myc-tagged N-and C-terminal truncations of Pex14 were tested for localization to LDs or peroxisomes in +Oleate cells (Figure 4G).…”
Section: Resultsmentioning
confidence: 99%
“…Pex3, Pex13, and Pex14 are all bilayer membrane spanning proteins inserted into PPVs, in a process that likely requires Pex19 (Götte et al, 1998; Pinto et al, 2006). When inserted into the peroxisome membrane, the Pex14 C-terminal domain faces the cytoplasm (Barros-Barbosa et al, 2019; Reuter et al, 2021). One possible model is that Pex14 at the LD surface is embedded within vesicles and the C-terminal of Pex14 interacts with an LD-resident protein, or that the C-terminal of Pex14 that can interact directly with the LD surface.…”
Section: Discussionmentioning
confidence: 99%